PROFESSIONALISM PHYSICAL EDUCATION TEACHER BASED ON PEDAGOGIC PERFORMANCE - Hengki Kumbara; Bayu Iswana; Husni Fahritsani (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2021)
The purpose of this study was to determine students' perceptions of the professionalism of PJOK teachers in terms of pedagogical performance aspects in the SMA Negeri in Suak Tapeh Banyuasin District. This type of research is a quantitative research with survey techniques. The population and sample amounted to 40 people divided into two schools, namely 20 students of SMA Negeri 1 Suak Tapeh, 20 students of SMK Negeri 1 Suak Tapeh. Data collection using a research questionnaire. The results showed that the students' perceptions on the aspects of mastery of the characteristics of students were 67% with the fairly professional category, the theoretical mastery aspect was 72% with the professional category, 64% mastery of curriculum development with the sufficiently professional category, the ability to educate 81% with the professional category, development. The potential of students is 78% with the professional category, the communication pattern is 68% with the fairly professional category, assessment and evaluation is 79% with the professional category. Meanwhile, the professionalism of teacher pedagogic performance based on students' perceptions was 73% in the professional category.